Mental well-being of nurses at an urgency and emergency hospital - Nascimento, Rafael dos Santos; Martins, Cristiane Maria Alves; Brandão, Thyara Maia; Ribeiro, Mara Cristina (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2021)
Objective: to identify nurses’ self-perception about the factors that interfere with their mental well-being during the work process in an urgency and emergency hospital. Method: a field study with a qualitative approach conducted by means of interviews with nurses in the red wards (trauma and clinic) of a reference hospital, located in the state of Alagoas. Results: there are several factors that positively or negatively affect the mental well-being of nurses, who work in urgency and emergency hospitals. The worker’s mental illness process is unique, complex, and dynamic, in addition to being multifactorial. Thus, even with several negative factors found in the workplace, the positive factors can stand out and minimize the unhealthy interferences suffered by professionals. Conclusion: it is important that nurses and institutions are sensitive about this topic, which is still neglected, so that strategies compatible with the reality of each location and which can provide quality of life and mental well-being at work are built.